Relationships Between Narrow Personality Traits and Self-Regulated Learning Strategies: Exploring the Role of Mindfulness, Contingent Self-Esteem, and Self-Control - Felicitas Opelt; Malte Schwinger (SAGE Publishing, 2020)
Based on Boekaerts' dual-processing self-regulation model, our study seeks to examine to what extent narrow personality traits are associated with different aspects of self-regulated learning. We approach this research question by examining the relationships of the narrow personality traits mindfulness, contingent self-esteem (domain academic competence), and self-control with various self-regulated learning strategies, emotion regulation strategies, and affective well-being during learning in a sample of N = 588 university students. Path analysis revealed the selected narrow personality traits to be significantly related to a variety of the investigated self-regulated learning variables, with more relationships to self-control and the contingent self-esteem domain academic competence than to mindfulness. Our study overall contributes to the understanding of how the selected narrow personality traits of students are associated with various aspects of their self-regulated learning behavior. Practical implications for promoting self-regulated learning via training (self-control) and counseling services (contingent self-esteem) are discussed.